The Difference Of Physical Activity In Obese And Non-Obese Adolescents Of Permai Pluit Junior High School Students - Tena Djuartina; Andreas Steven; Sylvia Wijaya; Syarief Darmawan (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
The Difference Of Physical Activity In Obese And Non-Obese Adolescents Of Permai Pluit Junior High School Students Obesity is defined as abnormal or excessive fat accumulation that presents a risk to health. According to the World Health Organization (WHO), at least 2.8 million people die every year as a result of being obesity. The prevalence of obesity in women is higher (26.9%) than males (16.3%) and according to RISKESDAS (2013) showed that the prevalence of obesity in adolescents, aged 13-15, in Indonesia amounted to 2.5%. The aim of this study is to assess the differences of physical activity in obese and non-obese adolescents. The design of this research is descriptive analytical research with case control categorical approach. The sample is the entire of Permai Pluit Junior High School student. The level of physical activity is assessed by using the Baecke Questionnaire, which has been modified and is statistically analyzed using Chi square test with Fischer Exact for an alternative test. All students in Permai Pluit Junior High School have varying levels of activity. The obese students in Permai Pluit Junior High School are amounted to 14.44% and there is significant difference between physical activity and nutritional status (p = 0.011). The level of physical activity that is most often committed by the girl students is medium intensity (34,12%) as well as by the boy students is severe intensity (25,98%). Conclusion there is significant difference between physical activity and nutritional status among adolescents of Permai Pluit Junior High School students.